Encapsulated Curcuma aeruginosa: Inhibition Method of Bitter Receptor Cells from The Perspective of Wall Formation - Sihombing, Monang; Ananingsih, Victoria Kristina (Talenta Publisher, 2018)
Curcuma aeruginosa is one of the herbs with health benefits and has been used in traditional medicine, has the characteristic bitter taste, so that limited use was. The formation of walls in the active component coating process can minimize direct contact of bitter receptor cells in the oral peripherals so the perception of bitterness can be reduced. This study used a variation of the WPI concentration as the coating wall materials 10%, 15% and 20%. Formation of coating walls was analyzed using SEM later in the sensory test for effectiveness decreased level of bitterness. The addition of 10% WPI results in the best wall formation was in Curcuma aeruginosa, which could decrease perception of significant bitterness. In contrast to the addition of WPI 15% and 20% were found in an oval shape, craters and ruptures form on coating wall, reducing the protection of the core component and contact with bitter receptor cells in the oral peripheral resulting in bitters taste perception increasing.